Measurement of the branching fraction ratios R(D+) and R(D[ast]+) using muonic τ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Glaser, Fabian; Günther, Paul André; et al. (Physical review letters, 2025)
The branching fraction ratios of ¯𝐵0→𝐷+⁢𝜏−⁢¯𝜈𝜏 and ¯𝐵0→𝐷*+⁢𝜏−⁢¯𝜈𝜏 decays are measured with respect to their muonic counterparts, using a data sample corresponding to an integrated luminosity of 2.0 fb−1 collected by the LHCb experiment in proton-proton collisions at √𝑠 =13 TeV. The reconstructed final states are formed by combining 𝐷+ mesons with 𝜏−→𝜇−⁢¯𝜈𝜇⁢𝜈𝜏 candidates, where the 𝐷+ is reconstructed via the 𝐷+ →𝐾−⁢𝜋+⁢𝜋+ decay. The results are 𝑅⁡(𝐷+)=0.249±0.043±0.047, 𝑅⁡(𝐷*+)=0.402±0.081±0.085, where the first uncertainties are statistical and the second systematic. The two measurements have a correlation coefficient of −0.39 and are compatible with the standard model.
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, G. Frau, F.C. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov und weitere 1053
Im Titel sind die Zeichen "+" und "[ast]" hochgestellt
Im Titel ist [ast] als Tropfensternchen (englisch: teardrop-spoked asterisk) dargestellt
Gesehen am 20.10.2025